A review of industrial waste heat recovery system for power generation with Organic Rankine Cycle: Recent challenges and future outlook. (10th March 2021) - Loni, Reyhaneh; Najafi, Gholamhassan; Bellos, Evangelos; Rajaee, Fatemeh; Said, Zafar; Mazlan, Mohamed
Abstract: Waste heat recovery is an effective way to reuse waste energy in order to produce useful energy products. This technique aids in the reduction of CO2 emissions and to create sustainable and efficient systems. The objective of the present review paper is to summarize and to discuss the studies about waste heat recovery with the organic Rankine cycle (ORC). The ORC is a usual choice in waste heat recovery technologies because this cycle can operate with low, medium, and high-temperature heat source and so this cycle presents high flexibility and compatibility with waste heat. The novelty of this work is based on the investigation of different aspects of the examined technology and also the investigation of the cogeneration systems, which are based on the waste heat recovery with ORC. The results of this work indicate that the exploitation of waste heat is an attractive way to produce electricity efficiently. The cogeneration with waste heat is also an alternative design with promising results because it can lead to high overall efficiencies and optimal utilization of waste energy.